A escrita na psicose e seus efeitos no encontro com um psicanalista na atenção psicossocial - Andréa Máris Campos Guerra (Arquivos Brasileiros de Psicologia, 2009)
The text begins with a clinician case of psychosis, treated by the public mental health service, where the subject had developed by himself a strategy of treatment that includes the writing. We propose a discussion between the Psychoanalysis and the Mental Health, and then we discuss it based on Jacques Lacan's hypothesis for the writing on psychosis cases. We meet three possibilities: the idea of stereotypy and its contrary, the creative process, by the 1930s decade; the idea of a name's writing by the 1960s decade and finally the idea of the letter's writing by the 1970s decade. Coming back to the case, we have tried to extract the consequences of the writing in this case and a treatment direction for other cases.